Antibiotic and Desiccation Resistance of Cronobacter sakazakii and C. malonaticus Isolates from Powdered Infant Formula and Processing Environments - Fei, Peng; Jiang, Yujun; Feng, Jing; Forsythe, Stephen J.; Li, Ran; Zhou, Yanhong; Man, Chaoxin (Frontiers in Microbiology, 2017)
This study evaluated the antimicrobial and desiccation resistance of Cronobacter sakazakii and C. malonaticus isolates from powdered infant formula and processing environments. The antimicrobial susceptibility tests showed that the 70 Cronobacter strains, representing 19 sequence types, were susceptible to the most of the antibiotics except for amoxicillin-clavulanate, ampicillin and cefazolin. Furthermore, the growth of six C. sakazakii and two C. malonaticus strains from different sequence types (STs) in hyperosmotic media was measured. The growth of the two C. sakazakii strains (CE1 and CE13) from the neonatal pathovars ST4 and ST8, were significantly higher (p<0.05) than that of other strains. C. malonaticus strain CM35 (ST201) was the slowest grower in all strains, and most could not grow in more than 8% NaCl solution. Also the survival of these strains under desiccation conditions was followed for one year. The viable count of Cronobacter spp. under desiccation conditions was reduced on average by 3.02 log cycles during one year, with CE13 (ST8) being the most desiccation resistant strain. These results will improve our understanding of the persistence of the two closely related species C. sakazakii and C. malonaticus which are of concern for neonatal and adult health.